The protocol book for intensive care - Kumar, Soumitra (Jaypee Brothers Medical Publishers (P) Ltd, 2014)
The Fourth Edition of The Protocol Book for Intensive Care is indeed a praise-worthy compendium of contemporary guidelines on the management of acute cardiac emergencies and related common acute medical problems. The guidelines have been supported by relevant scientific evidence and appropriate class of recommendation, as is the current practice